Clinico-Epidemiological Presentation and Treatment Outcome of Peripheral T-Cell Lymphoma, Not Otherwise Specified (PTCL-NOS): A Single-Institution Experience - Roy, Partha Sarathi; Mallik, Sreya; Sarma, Anupam; Hazarika, Munlima; Reddy, Raghavender; D, Nithin Raj (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: Peripheral T-cell lymphomas (PTCLs) are aggressive malignant lymphoproliferative disorders, accounting for 10-15% of all non-Hodgkin's lymphomas (NHLs). PTCL, not otherwise specified (PTCL-NOS), comprises approximately 6% of all NHLs and does not meet the criteria for other mature peripheral T-cell lymphomas as defined by the World Health Organization (WHO) classification. With limited long-term data evaluating the outcome of PTCL-NOS in the Indian population, this study aimed to determine the clinico-epidemiological profile and treatment outcomes of patients with PTCL-NOS at a cancer care center in Northeast India. Material and Methods: This retrospective observational analysis was performed on the medical records of patients diagnosed with PTCL-NOS between January 2015 and December 2018 at Dr. B. Borooah Cancer Institute. Results: Our study evaluated 53 patients with PTCL-NOS, with a mean age at presentation of 45.3 years (SD ± 16.3 years). The majority of patients (77.3%) presented with advanced stage (III/IV) disease, with bone marrow involvement in 35.8% of patients. B-symptoms were present in 58.4% of patients. Extra-nodal sites of involvement were observed in 64.1% of patients. Anthracycline-based chemotherapy regimens were the most commonly used in the frontline setting (71.6% of patients). Radiation therapy (involved field radiotherapy [IFRT]) was received by 26.4% of patients. The overall response rate (ORR) to first-line chemotherapy was 94.3%, with complete response (CR) achieved by 62.3% of patients. Twenty-nine (58%) patients experienced relapsed or progressive disease. With a median follow-up duration of 38 months, the 3-year progression-free survival (PFS) rate and 3-year overall survival (OS) rate were 27.6% and 33.9%, respectively. The median PFS was 22 ± 3.3 months, and the median OS was 28 ± 7.1 months. Conclusion: PTCL-NOS represents an aggressive subtype of NHL with limited therapeutic options and poor outcomes. Proper treatment adherence and the availability of newer therapeutic options are crucial for enhancing overall patient outcomes.